A Novel Lipoprotein Lipase Mutation in an Infant With Glycogen Storage Disease Type-Ib and Severe Hypertriglyceridemia - Wang, Fengyu; Wang, Fengli; Zhou, Xiaojun; Yi, Yingjie; Zhao, Jie (Frontiers in Pediatrics, 2021)
Glycogen storage disease (GSD) Ib is a rare genetic metabolic disorder caused by gene mutation in glucose 6-phosphate transport gene SLC37A4 (OMIM#602671). This study aimed to explore the association between a novel lipoprotein lipase (LPL) mutation and severe hypertriglyceridemia in a GSD Ib infant with severe hypertriglyceridemia. A 5-month-old girl was admitted to our hospital because of repeated episodes of low-grade fever over the past month and because of neutropenia. The patient was diagnosed with GSD Ib and severe hypertriglyceridemia based on clinical manifestations and laboratory test results. Next-generation sequencing and Sanger sequencing were then applied to DNA from the peripheral blood of the patient and her patients to analyze genes mutations. Pathogenicity prediction analysis was performed using Sorting Intolerant From Tolerant (SIFT) and PolyPhen-2 platforms. The results revealed that this infant carried a compound heterozygous variation in SLC37A4 gene, a c.1043T>C (p.L348P) mutation derived from her mother and a c.572C>T (p.P191L) mutation derived from her father. In addition, a novel c.483delA (p. A162Pfs*10) frameshift mutation was found in the patient’s LPL gene exon 4, which was derived from the heterozygous carrier of her father. The SIFT and PolyPhen-2 prediction programs indicated that these mutations were likely harmful. Medium-chain triglyceride milk and granulocyte colony-stimulating factor subcutaneous injection alleviated the symptoms. Our findings identified a novel LPL gene frameshift mutation combined with SLC37A4 gene compound heterozygous mutations in a GSD Ib infant with severe hypertriglyceridemia. .